2018
DOI: 10.3390/molecules23010075
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Analog DK1 Induces Apoptosis in Human Osteosarcoma Cells In Vitro through Mitochondria-Dependent Signaling Pathway

Abstract: Osteosarcoma is one of the primary malignant bone tumors that confer low survival rates for patients even with intensive regime treatments. Therefore, discovery of novel anti-osteosarcoma drugs derived from natural products that are not harmful to the normal cells remains crucial. Curcumin is one of the natural substances that have been extensively studied due to its anti-cancer properties and is pharmacologically safe considering its ubiquitous consumption for centuries. However, curcumin suffers from a poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The externalization of phosphatidylserine occurs due to the disintegration of the membrane structure, indicating that DK1 induced cell death via apoptosis in both HT29 and SW620 cells. These results are also in agreement with previous studies conducted on breast cancer cells and osteosarcoma cells, which concluded that DK1 induces cell death through the apoptosis pathway [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The externalization of phosphatidylserine occurs due to the disintegration of the membrane structure, indicating that DK1 induced cell death via apoptosis in both HT29 and SW620 cells. These results are also in agreement with previous studies conducted on breast cancer cells and osteosarcoma cells, which concluded that DK1 induces cell death through the apoptosis pathway [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…The effects of DK1 treatment towards HT29 and SW620 cells were further assessed by conducting qRT-PCR and human apoptosis proteome profiler. Apoptosis is mainly regulated by the caspase cascade and a family of apoptotic proteins called Bcl-2 family protein [ 16 , 18 ]. Caspase-3, caspase-8, and caspase-9 were chosen as these genes are involved in the caspase cascade that would then trigger the regulation of Bax and cytochrome c. The gene regulation of cyclin A and Cdk 2 genes were also assessed as they form a complex that plays an important role in the cell cycle progression at S phase, as shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin has been shown to play an anti-cancer effect in OS cells, its mediation can potentially be occurred via Notch-1 signaling inactivation, suggesting that curcumin is involved in upregulation of Notch-1 may be considered as a potential therapeutic strategy for OS [ 191 ]. It has been reported that apoptosis can be induced by Curcumin analog DK1 in human OS cells via mitochondria-dependent signaling, indicating its potential for future cancer treatment [ 192 ]. Moreover, Curcumin-loaded nanoparticles have been revealed to be involved in increasing apoptosis in OS cells [ 193 ].…”
Section: Identifying Os Stem Cell Populations As Therapeutic Targetsmentioning
confidence: 99%
“…Synthetic curcuminoid derivatives have, therefore, been developed by modifying the parent structure to improve anticancer potency. These analogs include DK1 [13], B63 [14], EF24 [15], WZ35 [16], and those with 1,4,6-trien-one function or trienones [17].…”
Section: Introductionmentioning
confidence: 99%